The platinum market: fundamentals affecting supply and demand - Mauve, Anton Christopher (My University, 2014)
The platinum market is best understood through a comprehensive analysis of supply and demand. Supply is most significantly affected by production constraints and the erratic draw-down in Russian stockpiles. Total world supply of platinum for 1998 amounted to 5.915 Moz, 64% of which was produced from the Bushveld Complex in South Africa. The remainder emanated from Russia, Zimbabwe, the United States, Canada and the recycling of autocatalysts. Supply is forecast to drop by 320 000 oz in 1999 due to a lower Russian export quota and reduced Zimbabwean production. Demand for platinum is unusual, in that it is sought after both as a store of wealth, and has properties that make it irreplaceable in a host of industrial applications. Current world demand for the metal is driven by a growing Eastern jewelry market and increased use in autocatalysts due to vehicle emissions legislation. Total world demand for 1998 amounted to 5.755 Moz. A predicted steady growth in the consumption of platinum for jewelry and existing applications, together with development of new uses, is expected to result in an annual 250 000 oz increase in demand for 1999 and 2000. The derived supply and demand balance for 1998 shows a small excess in supply relative to demand. This will be absorbed by inventories and is likely to have little affect on price, A significant shortfall of 410 000 oz, however, is predicted for 1999. This is likely to be followed by a further shortfall in 2000 and will drive up prices, impel consumers towards substitution and thriving and encourage producers to expand.
Keywords: Platinum--Supply and demand; Platinum mines and mining